A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 5 years ago
solve by using the substitution method
x+y=6
x+4y=3
anonymous
 5 years ago
solve by using the substitution method x+y=6 x+4y=3

This Question is Closed

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0From the first equation, x=6y. Substitute this value of x into the 2nd equation, you get: \[6y+4y=3 \implies 6+3y=3 \implies 3y=3 \implies y=1\] So, we have y=1. Now, substitute this value of y in equation (1) to get x: \[x1=6 \implies x=7\] That's the solution of the system is is x=7 and y=1

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0can you help me to sove some more ??please solve by the addition method 2x+y=11 xy=11

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0Ok, Can you add equation (1) to equation (2)?

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0You should add the x's together, the y's together and the constants together. That would give you: 3x=22 > x=22/3 Substitute this value of x in equation (2) to find y.

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0and i also need help to solve this one the last one 3x2y=12 5x+2y=4
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.